Nevus comedonicus with unusual bilateral band distribution around the neck. - Da-guang, Wang; Wen-yuan, Zhu (European Journal of Pediatric Dermatology, 2005)
A case of comedo nevus was presented, differing in certain respects from previous descriptions of this nevoid condition. The unusual feature of our case was bilateral band distribution around the neck.